Llama Llama Colors - Dewdney, Anna; Morrow, J. T. ([Place of publication not identified] : Viking books for Young Readers, 2021)
Llama Llama wants to paint but all he has is his lunch! Join the fun as he gets creative with his meal and makes a portrait of our favorite mama llama using orange carrots, green peas, and a few other items he sneaks from the fridge. Will Mama Llama be mad when she sees his colorful masterpiece?
Keywords: Fruit; Vegetables; Colors; Children; Rhyme